Sizing and operation of a residential PV-battery system: Rule-Based and real time vs optimization and perfect foresight - Sedano-Ruiz, Elena; Huete-Cubillo, Jesús; de-la-Vega-Rodríguez, Jorge; Martín-Rivas, Sebastián (IEEE, 2020)
Many residential customers are becoming prosumers, because of environmental concerns and falling prices of renewable generation technologies, as photovoltaic. In this context, typical residential installations consists of photovoltaic (PV) generation and batteries. Battery energy management poses a challenge because of the variability and uncertainty related to PV generation and customer consumption. Here, we propose easy to implement rules for the system (PV + battery) operation, to minimize the total cost for the customer. The main contribution is to use the rule-based operation for system sizing and operation, and to compare the results to those for an optimization based sizing and operation with perfect foresight. Based on this comparison, the value of information for the system operation is quantified and discussed. The optimization problem and the rule-based operation are applied to a case study for a residential customer in Southern Spain.
Keywords: Energía fotovoltaica - Generación; Recursos energéticos renovables; Battery; Photovoltaic generation; Rule-based operation; Optimization; Perfect foresight